The Mediating Role of Brand Trust in the Relationship between Social Media Marketing and Purchase Intention - Rizky Andhanu Prasetyo; Aulia Rahmadini Siregar; Tran Hoang Phuc (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study examines the mediating role of brand trust in the relationship between social media marketing and purchase intention. The rapid growth of social media platforms has transformed marketing communication and reshaped consumer decision making. Firms increasingly rely on social media marketing activities to influence consumer perceptions, engagement, and buying behavior. However, prior findings show that social media marketing does not always directly translate into purchase intention, indicating the need to explore underlying psychological mechanisms. This study adopts a quantitative explanatory approach to analyze how brand trust functions as a key mediator. Drawing on empirical evidence from recent studies, the model positions social media marketing as an antecedent of brand trust, which subsequently drives purchase intention. The findings confirm that social media marketing significantly enhances brand trust through interactive content, informativeness, and perceived credibility. Brand trust, in turn, exerts a strong and positive effect on purchase intention and partially mediates the relationship between social media marketing and purchase intention. These results highlight that trust formation is a critical pathway through which social media marketing strategies become effective. The study contributes to marketing theory by strengthening the trust-based mediation framework and offers practical implications for managers seeking to optimize social media investments to stimulate consumer purchase intention.